Apple and Pear Juices as Memory Boosters: Phytochemicals Analysis and Comparative Study between Natural Fruit Juices and Memantine (Bangladesh Journal of Medical Science, 2023)
Background: Our memory is a treasure, a recollection of various events from our entire life. But a number of factors like aging, stress, anxiety, depression, injury, certain disorders or use of some medications may decrease the efficacy of our brain thereby affecting our memory.Objectives: The intend of our study was to evaluate the effect of a well renowned memory enhancing drug memantine on memory with fruits like apple (Malusdomestica) which is speculated to be good for memory.Methods: This study also aimed to put forward the positive effects of pear (Pyruscommunis L.) juice on memory. While 2nd part of study included qualitative and quantitative phytochemical screenings of apple and pear with peels and without peels. For first part of study, in vivo testing has been done onto 4 groups, i.e. control group, reference group, test group A &test group B. Mice’s behavior was evaluated using two apparatus i.e. Elevated Plus Maze for 3 days & Novel Object Recognition Chamber for 2 days. While phytochemical analysis has been performed on the pericarp and mesocarp region of fresh fruits which were isolated, shade dried, blended and finely powdered.Result: Results prove that pear juice does impart positive effects on memory and can prove to be an alternative in the prevention of memory loss. Both tested fruits (apple& pear in juice/ liquid form), do pose remarkably positive effects on brain’s activity. Apple juice has shown more memory enhancing effects and was closer to that of our standard drug i.e. memantine. It can be concluded that apple and pear both contain flavonoids like quercetin and epicatechin, having antioxidant properties, which can help reverting or preventing the age-related oxidative degeneration of neurons.Conclusion: Although the memory enhancing effects of reference standard i.e. memantine is high as compare to our tested fruit juices but still it gives hope and evidenced that apple and pear juices can serve as memory enhancers to save our memory from deteriorating and active constituents from apples and pears could consider as excellent source for drug development and future pharmacological studies.Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 842-849